Improving the Outcome of Leukemia by Natural Killer Cell-Based Immunotherapeutic Strategies - Chouaib, Salem; Pittari, Gianfranco; Nanbakhsh, Arash; El Ayoubi, Hanadi; Amsellem, Sophie; Bourhis, Jean-Henri; Spanholtz, Jan (Frontiers in Immunology, 2014)
Blurring the boundary between innate and adaptive immune system, natural killer (NK) cells are widely recognized as potent anti-leukemia mediators. Alloreactive donor NK cells have been shown to improve the outcome of allogeneic stem-cell transplantation for leukemia. In addition, in vivo transfer of NK cells may soon reveal an important therapeutic tool for leukemia, if tolerance to NK-mediated anti-leukemia effects is overcome. This will require, at a minimum, the ex vivo generation of a clinically safe NK cell product containing adequate numbers of NK cells with robust anti-leukemia potential. Ideally, ex vivo generated NK cells should also have similar anti-leukemia potential in different patients, and be easy to obtain for convenient clinical scale-up. Moreover, optimal clinical protocols for NK therapy in leukemia and other cancers are still lacking. These and other issues are being currently addressed by multiple research groups. This review will first describe current laboratory NK cell expansion and differentiation techniques by separately addressing different NK cell sources. Subsequently, it will address the mechanisms known to be responsible for NK cell alloreactivity, as well as their clinical impact in the hematopoietic stem cells transplantation setting. Finally, it will briefly provide insight on past NK-based clinical trials.